Whole genome sequencing and characterization of Pantoea agglomerans DBM 3797, endophyte, isolated from fresh hop (Humulus lupulus L.) - Patakova, Petra; Vasylkivska, Maryna; Sedlar, Karel; Jureckova, Katerina; Bezdicek, Matej; Lovecka, Petra; Branska, Barbora; Kastanek, Petr; Krofta, Karel (Frontiers in Microbiology, 2024)
This paper brings new information about the genome and phenotypic characteristics of Pantoea agglomerans strain DBM 3797, isolated from fresh Czech hop (Humulus lupulus) in the Saaz hopgrowing region. Although P. agglomerans strains are frequently isolated from different materials, there are not usually thoroughly characterized even if they have versatile metabolism. The typical appearance characteristics of the strain include the formation of symplasmata in submerged liquid culture and the formation of pale yellow colonies on agar. The genetic information of the strain (in total 4.8 Mb) is divided between a chromosome and two plasmids. The strain lacks any CRISPR-Cas system but is equipped with four restriction-modification systems. The phenotypic analysis focused on growth under both aerobic and anaerobic conditions, as well as traits associated with plant growth promotion. At both levels (genomic and phenotypic), the production of siderophores, indoleacetic acid-derived growth promoters, gluconic acid, and enzyme activities related to the degradation of complex organic compounds were found. Extracellular gluconic acid production under aerobic conditions (up to 8 g/l) is probably the result of glucose oxidation by the membrane-bound pyrroloquinoline quinone-dependent enzyme glucose dehydrogenase. The strain seems to have a considerable potential for application in agriculture as a support culture for hop growth.